Motivational Needs and Intent to Stay of Social Enterprise Workers - Caringal-Go, Jaimee Felice (Archīum Ateneo, 2018)
Using a needs theory framework, this study investigated motivations of social enterprise workers and their intent to stay using a sequential mixed exploratory design. Factor analysis of survey data elicited two factors corresponding to intrinsic and extrinsic needs. The extent to which these needs are met predicted intent to stay for both staff level employees and managers/founders. However, results showed differences between job levels on the extent to which intrinsic needs are met. Unique needs that appear to be an artifact of the nature of social enterprises and context are examined. Human resource management implications for social enterprises are discussed.